2017
DOI: 10.5851/kosfa.2017.37.5.698
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Irradiation Sources on Quality Attributes of Low-salt Sausage during Refrigerated Storage

Abstract: This study was performed to investigate the impacts of irradiation sources on quality attributes of low-salt sausage during refrigerated storage. Control sausage was prepared with 1.5% sodium chloride (NaCl), whereas low-salt sausage was formulated with 0.75% NaCl (a 50% reduction; L-control). Sausage samples were vacuum-packaged, and low-sausages were irradiated with gamma-ray, electron-beam and X-ray at 5 kGy, respectively. The samples were stored at 4°C for 28 d to determine changes in quality attributes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Numerous studies have attempted to prepare salt mixtures via partial substitution of NaCl by KCl, CaCl 2 , or MgCl 2 and natural ingredients such as seaweeds [7,8]. Although these strategies could reduce the content of Na in meat products, they revealed problems of bitterness and metallic flavors [3].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have attempted to prepare salt mixtures via partial substitution of NaCl by KCl, CaCl 2 , or MgCl 2 and natural ingredients such as seaweeds [7,8]. Although these strategies could reduce the content of Na in meat products, they revealed problems of bitterness and metallic flavors [3].…”
Section: Introductionmentioning
confidence: 99%
“…The food irradiation technique, with its excellent sterilization effect, has been used in several low-salt foods that may be vulnerable to spoilage due to microbial growth [ 13 ]. Particularly in processed meat products with relatively low salt concentrations (around 2%), gamma-ray treatment at 2 kGy was found to reduce aerobic mesophilic microbial counts from 7.6 to 1.2 log 10 counts/g under 7 °C storage conditions for 1 week.…”
Section: Alternative Processing Techniquesmentioning
confidence: 99%
“…Particularly in processed meat products with relatively low salt concentrations (around 2%), gamma-ray treatment at 2 kGy was found to reduce aerobic mesophilic microbial counts from 7.6 to 1.2 log 10 counts/g under 7 °C storage conditions for 1 week. Recently, Song et al [ 13 ] reported that the three ionizing sources (gamma rays, electron beams, and X-rays) at 5 kGy had a positive impact on the microbial safety (absence of aerobic microbes, coliforms and Enterobacteriaceae, and Pseudomonas spp.) of low-salt emulsion sausages (0.75% NaCl) during 4 weeks of chilled storage.…”
Section: Alternative Processing Techniquesmentioning
confidence: 99%
See 2 more Smart Citations